Sistem Informasi Lembaga Penjamin Mutu (LPM) pada AMIK Luwuk Banggai Berbasis Web - H. Godang, Randy; Yogi Pratama, I Made; Satanga, Febriani; Gita, Putri; Nasir, Muh.; Putra Yasa, I Ketut; Putu Rika Permana, I Gusti (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Quality Assurance Unit (LPM) plays a vital role in maintaining and improving academic quality and governance in higher education institutions. At AMIK Luwuk Banggai, however, the management of quality documents, accreditation instruments, and internal audit reports is still carried out manually, leading to delays, duplication, and difficulties in retrieving data. These issues negatively affect the effectiveness of the Internal Quality Assurance Sistem (SPMI), which is expected to support the achievement of national higher education standards. This study aims to design and develop a web-based Quality Assurance Information Sistem that facilitates integrated, fast, and accurate management of quality data. The sistem was developed using the waterfall model, which consists of requirements analysis, sistem design, implementation, and testing. Requirement analysis was conducted through interviews and observations of LPM’s workflows. The sistem design was carried out using the Data Flow Diagram (DFD) approach to model business process flows and the Entity Relationship Diagram (ERD) to design the database implemented in MySQL, while the implementation was carried out using a PHP-based web framework. The results of this study indicate that the developed sistem can simplify the management of quality documents, internal audit reporting, and real-time monitoring of quality standards. In addition, the sistem supports centralized data storage and minimizes the risk of document loss. Testing involving LPM staff and lecturers revealed that the sistem was considered effective, user-friendly, and capable of accelerating the preparation of quality assurance reports. The implication of this research is the availability of a digital platform that enhances quality management processes at AMIK Luwuk Banggai and can serve as a reference for the development of quality assurance sistems in other higher education institutions.